Effect of Impurities in the Physical-Chemical Properties of a Copper Mineral Leaching Solution - Navarro-Donoso, P; Vargas-Riquelme, C; Ramirez-Munoz, C (UNIV PEDAGOGICA & TECNOLOGICA COLOMBIA, 2016)
The physical and chemical properties of a copper leaching solution were quantified and analyzed in presence of high concentrations of chlorine, aluminum and magnesium. The properties tested were the density, viscosity and dissolved oxygen. The effect of the viscosity over time of phase separation in solvent extraction was also evaluated. The concentrations used of chlorine were 20, 30 and 50 g/L, aluminum 7, 15 and 23 g/L and finally the magnesium of 6, 14 and 22 g/L. The temperatures tested were 25, 35 and 45 degrees C. The results showed that the presence of impurities produces a significant impact on the viscosity and only small changes in density. Chlorine is the impurity with less impact, followed by magnesium, and aluminum producing the greatest impact. The temperature increase reduces the impact of these elements. The presence of impurities causes a decrease in dissolved oxygen concentration. In solvent extraction, an increase in viscosity produces longer times of phase separation.